Air quality and climate benefits of long-distance electricity transmission in China. (13th June 2017) - Peng, Wei; Yuan, Jiahai; Zhao, Yu; Lin, Meiyun; Zhang, Qiang; Victor, David G; Mauzerall, Denise L
Abstract: China is the world's top carbon emitter and suffers from severe air pollution. It has recently made commitments to improve air quality and to peak its CO2 emissions by 2030. We examine one strategy that can potentially address both issues—utilizing long-distance electricity transmission to bring renewable power to the polluted eastern provinces. Based on an integrated assessment using state-of-the-science atmospheric modeling and recent epidemiological evidence, we find that transmitting a hybrid of renewable (60%) and coal power (40%) (Hybrid-by-wire) reduces 16% more national air-pollution-associated deaths and decreases three times more carbon emissions than transmitting only coal-based electricity. Moreover, although we find that transmitting coal power (Coal-by-Wire, CbW) is slightly more effective at reducing air pollution impacts than replacing old coal power plants with newer cleaner ones in the east (Coal-by-Rail, CbR) (CbW achieves a 6% greater reduction in national total air-pollution-related mortalities than CbR), both coal scenarios have approximately the same carbon emissions. We thus demonstrate that coordinating transmission planning with renewable energy deployment is critical to maximize both local air quality benefits and global climate benefits.